X-ray fluorescence data of the varved sediment record (HZM19) from Holzmaar, Germany - Stella Birlo; María Luján García; Bernd Zolitschka (PANGAEA, 2024)
The elemental composition of the composite sediment record from HZM19 was obtained using the ITRAX XRF Core Scanner at the GEOPOLAR lab (University of Bremen) using a Cr tube with the following settings: exposure time: 5 s, voltage: 30 kV, and current: 50 mA. The step size was set to 200 μm. Prior to measurements and due to scanning times >7 h, core sections were covered with plastic foil (Chemplex Thin-Film). The dataset was cleaned following measurements, i.e. only data points remain that pass the following conditions: 1. counts per seconds >39.000; 2. MSE <15, and 3. validity equals 1. All values are provided in counts (cts). Here only the continuous XRF records of the composite profile is documented. Ages refer to Birlo et al. (2023) and the related dataset is Model D available via doi:10.1594/PANGAEA.949292.